The Effectiveness of Biostimulation, Bioaugmentation and Sorption-Biological Treatment of Soil Contaminated with Petroleum Products in the Russian Subarctic - Vladimir A. Myazin; Maria V. Korneykova; Alexandra A. Chaporgina; Nadezhda V. Fokina; Galina K. Vasilyeva (Microorganisms, 2021)
The effectiveness of different bioremediation methods (biostimulation, bioaugmentation, the sorption-biological method) for the restoration of soil contaminated with petroleum products in the Russian Subarctic has been studied. The object of the study includes soil contaminated for 20 years with petroleum products. By laboratory experiment, we established five types of microfungi that most intensively decompose petroleum hydrocarbons: Penicillium canescens st. 1, Penicillium simplicissimum st. 1, Penicillum commune, Penicillium ochrochloron, and Penicillium restrictum. One day after the start of the experiment, 6 to 18% of the hydrocarbons decomposed: at 3 days, this was 16 to 49%; at 7 days, 40 to 73%; and at 10 days, 71 to 87%. Penicillium commune exhibited the greatest degrading activity throughout the experiment. For soils of light granulometric composition with a low content of organic matter, a more effective method of bioremediation is sorption-biological treatment using peat or granulated activated carbon: the content of hydrocarbons decreased by an average of 65%, which is 2.5 times more effective than without treatment. The sorbent not only binds hydrocarbons and their toxic metabolites but is also a carrier for hydrocarbon-oxidizing microorganisms and prevents nutrient leaching from the soil. High efficiency was noted due to the biostimulation of the native hydrocarbon-oxidizing microfungi and bacteria by mineral fertilizers and liming. An increase in the number of microfungi, bacteria and dehydrogenase activity indicate the presence of a certain microbial potential of the soil and the ability of the hydrocarbons to produce biochemical oxidation. The use of the considered methods of bioremediation will improve the ecological state of the contaminated area and further the gradual restoration of biodiversity.